2016
DOI: 10.1159/000452208
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Infiltrative Hepatocellular Carcinoma with Portal Vein Tumor Thrombosis Completely Cured by Transcatheter Arterial Chemoembolization: Case Report with 8-Year Follow-Up

Abstract: Hepatocellular carcinoma (HCC) is the most common type of liver cancer and its treatment options are determined by shape, liver function, loci, and stages of cancer. Diffuse type of infiltrative HCC accompanied by portal vein tumor thrombosis (PVTT) has the poorest prognosis among other HCCs and there are no other prominent treatment options than systemic chemotherapy. In this study, we report a case of a 56-year-old man with diffuse infiltrative HCC accompanied by PVTT who achieved complete remission for 8 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…According to case report on Gastroenterology, a 56 year old man with HCC accompanied by PVTT who achieved complete remission for 8 years after receiving conventional TACE [11]. Herein, we report a case of a 60 year-old man with HCC accompanied by metastasis of Rt.…”
Section: Discussionmentioning
confidence: 98%
“…According to case report on Gastroenterology, a 56 year old man with HCC accompanied by PVTT who achieved complete remission for 8 years after receiving conventional TACE [11]. Herein, we report a case of a 60 year-old man with HCC accompanied by metastasis of Rt.…”
Section: Discussionmentioning
confidence: 98%
“… 18 Intra-arterial therapy (IAT) such as drug-eluting beads transcatheter arterial chemoembolization, conventional transcatheter arterial chemoembolization, or systemic chemotherapy like sorafenib is beneficial to these patients. 19 A retrospective study by Kneuertz et al 13 on the assessment of the presentation of diffuse HCC, treatment, and outcomes identified IAT to be a safer option for patients with infiltrative HCC with median survival at 1 and 3 years identified to be 49% and 34%, respectively. This is contrary to the study by Lopez et al, which reported 16% death within 30 days in IAT-treated infiltrative HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because most people with infiltrative HCC present at an advanced stage and have major vascular invasion at presentation (18,19,21,23) , surgical resection and transplantation are usually considered unfeasible (18,19,53) . The role of intra-arterial therapy in patients with infiltrative HCC is controversial according to current conflicting research (23,(54)(55)(56) . Sorafenib, a multi-target tyrosine kinase inhibitor, was the first drug approved for the first-line treatment of advanced HCC and has shown favorable results to date (57)(58)(59)(60)(61) .…”
Section: Discussionmentioning
confidence: 99%